c-Rel Is Required for IL-33-Dependent Activation of ILC2s - Zaini, Aidil; Fulford, Thomas S.; Grumont, Raelene J.; Runting, Jessica; Rodrigues, Grace; Ng, Judy; Gerondakis, Steve; Zaph, Colby; Scheer, Sebastian (Frontiers in Immunology, 2021)
Group 2 innate lymphoid cells (ILC2s) are emerging as important cellular regulators of homeostatic and disease-associated immune processes. The cytokine interleukin-33 (IL-33) promotes ILC2-dependent inflammation and immunity, and IL-33 has been shown to activate NF-κB in a wide variety of cell types. However, it is currently unclear which NF-κB members play an important role in IL-33-dependent ILC2 biology. Here, we identify the NF-κB family member c-Rel as a critical component of the IL-33-dependent activation of ILC2s. Although c-Rel is dispensable for ILC2 development, it is critical for ILC2 function in the lung. C-Rel-deficient (c-Rel–/–) mice are resistant to papain- and IL-33-induced lung inflammation. We show that the absence of c-Rel results in reduced IL-33-dependent expansion of ILC2 precursors and lower levels of IL-5 and IL-13 cytokine production by mature ILC2s in the lung. Together, these results identify the IL-33-c-Rel axis as a central control point of ILC2 activation and function.